Breast Milk Prefusion F Immunoglobulin G as a Correlate of Protection Against Respiratory Syncytial Virus Acute Respiratory Illness. (10th August 2018) - Mazur, Natalie I; Horsley, Nicole M; Englund, Janet A; Nederend, Maaike; Magaret, Amalia; Kumar, Azad; Jacobino, Shamir R; de Haan, Cornelis A M; Khatry, Subarna K; LeClerq, Steven C; Steinhoff, Mark C; Tielsch, James M; et al.
Abstract: Background: Transplacental respiratory syncytial virus (RSV) antibody transfer has been characterized, but little is known about the protective effect of breast milk RSV-specific antibodies. Serum antibodies against the prefusion RSV fusion protein (pre-F) exhibit high neutralizing activity. We investigate protection of breast milk pre-F antibodies against RSV acute respiratory infection (ARI). Methods: Breast milk at 1, 3, and 6 months postpartum and midnasal swabs during infant illness episodes were collected in mother–infant pairs in Nepal. One hundred seventy-four infants with and without RSV ARI were matched 1:1 by risk factors for RSV ARI. Pre-F immunoglobulin A (IgA) and immunoglobulin G (IgG) antibody levels were measured in breast milk. Results: The median breast milk pre-F IgG antibody concentration before illness was lower in mothers of infants with RSV ARI (1.4 [interquartile range IQR, 1.1–1.6] log10 ng/mL) than without RSV ARI (1.5 [IQR, 1.3–1.8] log10 ng/mL) ( P = .001). There was no difference in median maternal pre-F IgA antibody concentrations in cases vs controls (1.7 [IQR, 0.0–2.2] log10 ng/mL vs 1.7 [IQR, 1.2–2.2] log10 ng/mL, respectively; P = .58). Conclusions: Low breast milk pre-F IgG antibodies before RSV ARI support a potential role for pre-F IgG as a correlate of protection against RSV ARI. Induction of breast milk pre-F IgG may be a mechanism of protection for maternal RSV vaccines. Abstract : Low breast milk prefusion (pre-F) immunoglobulin G (IgG) antibodies before respiratory syncytial virus (RSV) acute respiratory infection (ARI) supports a potential role for pre-F IgG as a correlate of protection against RSV ARI. Induction of breast milk pre-F IgG may be a mechanism of protection for maternal RSV vaccines.